Multidimensional assessment of Game Transfer Phenomena: Intrusive cognitions, perceptual distortions, hallucinations and dissociations - Ortiz de Gortari, Angelica B.; Diseth, Åge (Frontiers in Psychology, 2022)
Game Transfer Phenomena (GTP) refers to a cluster of involuntary phenomena related to playing videogames, including sensory and cognitive intrusions, transient changes in perception and self-agency. The Game Transfer Phenomena Scale (GTPS) has been used to measure the frequency of GTP with respect to five factors. The present study aimed to validate an instrument for assessing the multiple dimensions of GTP (GTP-MDS) that helps clarify the distinction between GTP experiences. GTP were contextualized onto the spectrum of intrusive cognitions, perceptual distortions, and dissociations. The relationship between GTP, involuntary phenomena without game content (INVWG) in terms of e.g., hallucinations and perceptual distortions, and game-biased perceptions (GBPA), as well as the positive and negative impact of GTP and level of distress were also examined. The data were collected using a survey (N = 1,301, male 83.4%, mean age = 28.14). Separate confirmatory factor analyses of the dimensions of “inner intrusions/misperceptions,” “outer intrusions/distortions,” and “dissociations/mix-ups” produced acceptable fit indices. The findings show that phenomena manifesting as internal experiences are more common, while those manifesting as externalized intrusions are less common. Correlations between the GTP dimensions, INVWG, and GBPA, such as the insertion of game elements in thoughts, perceptions, and dreams, supported convergent validity. The correlations between the GTP dimensions and hours played supported criterion validity. Distress was correlated with outer intrusions and dissociations/mix-ups, but not with inner intrusions. Taken together, these results support the validity and reliability of the proposed assessment of GTP constructs.